The Begonia flora of Gunung Mulu and Gunung Buda National Parks, Sarawak, Borneo, including five new species - Sang, Julia; Kiew, Ruth; Yiing, Ling Chea (Phytotaxa, 2018)
An account of the twenty Begonia species from the Gunung Mulu and Gunung Buda National Parks is presented with illustrated descriptions of five new species (Begonia argentii, B. jokwaniana, B. lansatensis, B. muluensis and B. vulgarioides) and one new record (Begonia chlorocarpa Irmsch. ex Sands). A key for their identification is provided.